Estimation of Genetic Parameter in New Plant Type Aromatic Rice Lines - Lestari, Angelita Puji; Abdullah, Buang; Junaedi, Ahmad; Aswidinnoor, Hajrial (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
Information on genetic variability and heritability of plant characters is important to support the rice selection program. A study was conducted to determine the genetic variability of characters and grain yields of 35 New Plant Type Rice Lines (NPTR) under two different environments, with varieties Ciherang and Sintanur as checks. The trials were conducted at two locations (Bogor and Pusakanagara, West Java) during dry season (DS) 2009 and wet season (WS) of 2009/2010. Each trial was arranged in a randomized block design (RBD) with three replications. Twenty one day-old rice seedlings of each entry were planted in 2 m x 5 m plots at a 20 cm x 20 cm plant spacing, one seedling per hill. Results of the combined analysis showed that strains, environments, and its interaction was significantly affecting the whole characters of NPTR. High variabilities were observed on genetic, heritability, and genetic advance characters among the new rice type lines, particularly on the number of productive tillers, total number of grains per panicle, and total grain yield. These three characters were positively correlated with rice grain yield, and could be used as indicators for superior lines.